Cognitive dysfunction after out-of-hospital cardiac arrest: Rate of impairment and clinical predictors. (August 2021) - Byron-Alhassan, Aziza; Collins, Barbara; Bedard, Marc; Quinlan, Bonnie; Le May, Michel; Duchesne, Lloyd; Osborne, Christina; Wells, George; Smith, Andra M.; Tulloch, Heather E.
Abstract: Background: The purpose of this study was to evaluate the rate and domains of cognitive impairment in out-of-hospital cardiac arrest (OHCA) survivors, as compared to patients who experienced a myocardial infarction (MI), and to explore mechanisms and predictors of this impairment. Methods and results: OHCA survivors with "good" neurological recovery (i.e., Cerebral Performance Categories Scale ≤ 2) ( n = 79), as well as a control group of MI patients ( n = 69), underwent a comprehensive neuropsychological assessment. Forty-three percent of OHCA survivors were cognitively impaired (in the lowest decile on a global measure of cognitive functioning). Rates of impairment were approximately six times higher in the OHCA group than the MI group. Attention, memory, language and executive function were affected. Downtime was a significant predictor of cognitive impairment; the interaction between downtime and immediate intervention was significant such that, at short downtimes, receiving cardiopulmonary resuscitation (CPR) or defibrillation within 1 min of collapse predicted less cognitive impairment. Conclusions: OHCA survivors – even those with seemingly good neurological recovery – are at risk for cognitive impairment. Cognitive rehabilitation may be an important consideration post-OHCA.